POLITICAL MEANING OF IMAGINATION - Merkinaitė, Simona (Politologija, 2015)
There are two ways of looking at the relationship between politics and imagination. Imagination is a capacity to create images and objects that directly cannot be perceived. As such imagination often is perceived as a capacity to create make-believes, taking us away from the reality, therefore imagination should have no role in the political world. Contrary to this position, one can overall deny the clear distinction between reality and imagination, due to the fact that political works is made from values, believes, myths, stories – all that separates the world of political from the world of nature. Both positions have their own faults. The first one ignores and fails to explain the various influences on the political – such as myths, beliefs, and religious arguments. This position largely treats policy knowledge as though it were a matter of rational calculation. The second – drives towards the Baudrillard-like view of the world made if simulacra and signs failing at the same time to draw a distinction between make-believes and the products of imagination that have real political effect. The objective of the article is to research the relationship between politics and imagination.This is done applying the functions of imagination to political sphere. Imagination helps to create “something that is not given directly”. Imagination therefore allows crossing the line between the imagined and the real. In the context of political world, different human experiences, first and foremost religious experiences are analyzed as allowing crossing the line between the rational domain of policy and its knowledge and the imagined. Religious experiences represent a world that has its own standard of reality affecting the political domain. We can talk about different realities then, made visible to us though different forms of imagination – scientific, art, religious, historical – all giving different answer to the question what is real and those different worlds collide in the political domain. Therefore it is argued that the political cannot have the clear distinction between the real and the imagined.Secondly, the capacity of imagination to introduce the distance between the reality and the imagined is discussed in the context of the political domain. This particular capacity of imagination is crucial for moral act, as seen in Kant, Smith, or Nussbaum. It is argued that the same need to introduce the distance between the moral agent and the decision to be made is applicable to political decisions. Here also the distance between the reality (such as social inequality) and the political metaphors shaping policy (such as social equality and freedoms) is discussed. Political reality is made from various metaphors, such as liberty, sovereignty, the will of people, which are objects of imagination as much as of knowledge or experience which makes the political reality not only as “something present”, but something that “we aspire to as a political entity”.Lastly, the capacity of imagination to connect different objects is discussed as a capacity connecting people with certain values or desires. It is argued that metaphors, history, and tradition – all are a source and at the same time a form of imagination that creates and separates different communal and political identities. The political entity cannot be separated from the capacity of its people to keep creating and recreating common identify.